Microbiological Surveillance and Antimicrobial Susceptibility Observations on Peritoneal Dialysis-Associated Peritonitis in an Outpatient German Reference Center - Annemarie Albert; Stefan Richter; Lisa C. Costello-Boerrigter; Philipp Stieger; Rainer Peter Woitas; Rüdiger C. Braun-Dullaeus; Christian Albert (Infectious Disease Reports, 2025)
Background: Peritonitis is a relevant complication in peritoneal dialysis (PD). The initial empirical antibiotic therapy depends on the center-specific distribution of microorganisms and the microbial susceptibility profiles. However, data on the locoregional germ spectrum in Germany are insufficient regarding the current recommended empirical antibiotic regimens of either cefepime as monotherapy or the combination of cefazolin and ceftazidime. Methods: This retrospective single-center study of routine clinical patient data analyzes the range of infecting organisms causing PD-associated peritonitis and their corresponding antimicrobial resistances during the 2015 to 2022 timeframe. We used Ordinary Least-Squares regression to model trends in the detection of microbiological spectrum samples. The ‘reporting of studies conducted using observational routinely collected health data’ (RECORD) statement was acknowledged. Results: There were 80 documented peritonitis episodes with 99 causal etiologies sampled. Of those, eighty-seven were bacterial, three were fungi (3%), eight had no microbial growth (8%), and one more had missing data. The largest group of microorganisms detected were Gram-positive bacteria (N = 56, 56.6%), predominantly sampled as Staphylococcacea, Enterococcaceae, and Streptococcaceae (Staphylococcus aureus, 14.1%). Gram-negative bacteria were found in 31.3% of samples (N = 31), predominantly Enterobacteriaceae (Escherichia coli, 9%). In total, 34 different microorganisms were identified. On one occasion, methicillin-resistant Staphylococcus epidermidis and one sample of multi-resistant Serratia marcescens were identified. Methicillin-resistant Staphylococcus aureus and vancomycin-resistant enterococci were not detected. Fungi were found in three peritonitis episodes. Regression analyses did not indicate changes in the general microbiological spectrum during the observational timeframe. The center-specific peritonitis rates were below the recommended rates of the International Society for Peritoneal Dialysis for all years studied. Conclusions: The recommended empiric therapy was suitable at our center, with a few exceptions for non-specific pathogens and for those with β-lactamases or enterococci. When there is no clinical response to empiric therapy, alternative antibiotics should be considered accordingly. The retrospective data are limited to the reported outcome measures.